Value relevance of earnings and book value of equity in Malaysia / Asyaari Elmiza Ahmad - Ahmad, Asyaari Elmiza (2006)
This study examines the changes in the value relevance and the effect of Asian financial crisis towards the explanatory power for both the accounting variables. By employing Ohlson's (1995) market valuation models, the results obtained are consistent with the prediction that there are mixed evidence of value relevance for earnings and book value of equity. The findings suggest that the value relevance of earnings and book value of equity are neither declining nor inclining for the Malaysian main board listed firms. This study also reveals that the value relevance of book value of equity is significantly larger than accounting earnings during the Asian financial crisis in 1997 and 1998. The findings are consistent with the prediction of prior studies that book value of equity is more relevant as compared to earnings in the event of financial difficulties facing the firms. As a conclusion, this study presents the evidence that the financial reporting systems in Malaysia are still relevant for the investors in the valuation of the market share prices.